HUMAN’S IMAGE IN POSMODERNISM - Прудиус, Р. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
The main peculiarities of image of human in postmodernism being are analyzed.